Experimental and numerical analysis of CFRP-strengthened finger-jointed timber beams. (July 2016) - Khelifa, M.; Celzard, A.; Oudjene, M.; Ruelle, J.
Abstract: Experimental and finite element (FE) studies of bending behaviour of finger-jointed timber ( Spruce ) beams reinforced with CFRP material were performed. Four-point bending tests with distinct reinforcement configurations were proposed in order to determine stiffness, ductility and strength values of strengthened finger-jointed timber beams. The experimental results obtained under flexure showed that the external bonding of CFRP increased the load-bearing capacity of finger-jointed Spruce timber beams. The numerical results presented here were based on the Cohesive Zone Model (CZM) available in Abaqus code, allowing the description of the progressive failure mode of the finger-jointed timber beams under flexural load. The FE models took the different material constitutive laws (wood, CFRP and adhesive) into account, including the bond-slip actions between finger-joints and CFRP-timber interface. The results in terms of load-mid span deflection and failure modes obtained experimentally and numerically were compared. Once the FE simulations were calibrated, the differences between experimental and predicted ultimate loads were around 4.5% only. A good agreement was therefore found, proving the relevance of the presented FE models to predict the load-bearing capacity and to capture the failure mode of CFRP-strengthened finger-jointed Spruce timber beams in bending.